PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING MELALUI PERMAINAN TENIS MEJA PADA HASIL BELAJAR SISWA SEKOLAH DASAR KELAS 5 - Siregar, Epi Supriyani; Sari, Ika Purnama; Imanuddin; Gulyanto, Bambang; Gunawan, Indra (Politeknik Negeri Jakarta, 2024)
This study aims to determine the effect of the Discovery learning learning model using table tennis games on the learning outcomes of 5th grade elementary school students. This type of research is quantitative research in the form of a Pre-Experimental Design with the type of One Group Pretest-Posttest. The population in this study were 5th grade elementary school students. The sample used in this study was 5th grade elementary school students consisting of 40 students. In determining the pretest and posttest, a validity test is carried out on the instrument questions which have been validated by the validator. The experimental method was used with a single group control pretest-posttest design to compare the learning outcomes of students who used the discovery learning method with groups of students who using conventional learning methods. The results showed that the group of students who took part in discovery learning through table tennis experienced a significant increase in learning outcomes compared to the group of students who received conventional learning. These findings indicate that the use of the discovery learning model with a table tennis game approach can be an effective alternative in improving the quality of learning in grade 5 elementary schools. After obtaining data from the results of the pretest and posttest, it was analyzed using the t-test. Obtained tcount = 25.817 with a significant level of 5% of 0.256. Because tcount = 25.81 > ttable = 0.256. Then Ha is accepted, this shows that the Discovery learning learning model with table tennis games has a significant effect on the learning outcomes of Grade 5 SD students. Based on the results of this research, the suggestion that can be conveyed is that the Discovery learning learning model using table tennis games can be used as an alternative for teachers to teach on the theme of my hero and other learning.